2023
DOI: 10.3892/ol.2023.13855
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment fibrinogen levels are associated with survival outcome in patients with cancer using immunotherapy as a second‑line treatment

Abstract: The present study aimed to investigate the predictive value of pretreatment fibrinogen (FIB) levels in patients with cancer who received immunotherapy as a second-line treatment. A total of 61 patients with stage III–IV cancer were included. The cut-off value of FIB for predicting overall survival (OS) was determined by receiver operating characteristic curve analysis. The prognostic value of pretreatment FIB on progression-free survival (PFS) and OS was determined by univariate and multivariate analyses. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…( 49 ) indicated that elevated pretreatment plasma fibrinogen levels are significantly associated with reduced survival rates in patients with solid tumors. In immunotherapy, initial fibrinogen concentrations correlate with patient prognoses ( 50 ). Further research has underscored fibrinogen’s involvement in cell migration, proliferation, angiogenesis, and hematogenous metastasis ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 49 ) indicated that elevated pretreatment plasma fibrinogen levels are significantly associated with reduced survival rates in patients with solid tumors. In immunotherapy, initial fibrinogen concentrations correlate with patient prognoses ( 50 ). Further research has underscored fibrinogen’s involvement in cell migration, proliferation, angiogenesis, and hematogenous metastasis ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%